PENGARUH KINERJA PENYULUH PERTANIAN TERHADAP PERILAKU PETANI SAYUR DI DESA TUENG KECAMATAN KUWUS BARAT (The Effect of Agricultural Extension Workers Performance on the Behaviors of Vegetable Farmers in Tueng Village, West Kuwus District) - Sudirman, Paulus Every; Ndau, Wensislaus Arman; Santu, Lorensius; Jemina, Helida (Jurnal Ilmiah Sosio Agribis, 2025)
This study aims to analyze the influence of the performance of agricultural extension workers on the behavior of vegetable farmers in Tueng Village, West Kuwus District. This research was carried out from March to May 2024. The types and sources of data are in the form of primary data and secondary data. Primary data was obtained from the results of interviews and direct survey results. Meanwhile, secondary data is data obtained by researchers through various existing sources. The population in this study is vegetable farmers in Tueng Village, West Kuwus District. Sample determination using Simple random sampling. The total respondents in this study were 35 farmers. Data analysis uses multiple linear regression analysis. Regression test is a statistical test used to measure the magnitude of the influence of independent variables on bound variables. The results of the study show that simultaneously the performance of agricultural extension workers affects the performance of vegetable farmers, this is evidenced by the calculated F value of 8.608 greater than the F value of the table of 4.396. Partially, the variables of motivational ability, frequency of counseling and communication ability have a significant effect on the behavior of vegetable farmers in Tueng Village, West Kuwus District, West Manggarai Regency.Keywords: Performance; Extension; Farmer Behavior